The Influence of Leadership Style and Rewards to Performance Assessment With Discipline as Intervening in PT Pelindo Multi Terminal Branch Belawan - Muhammad Ikhlas; Sri Rahayu; Kholilul Kholik (Utan Kayu Publishing, 2025)
This study aims to analyze the influence of Leadership Style and Reward on Performance Assessment with Discipline as an intervening variable in PT Pelindomulti Terminal Branch Belawan. This type of research is quantitative research with a causal associative approach. The population in this study is all organic and non-organic employees of PT Pelindomulti Terminal Branch Belawan which totals 276 employees. The determination of the number of samples refers to Arikunto's opinion by setting the sample at 25% and obtained 92 respondents who were selected using the proportionate stratified random sampling technique. The data collection technique was carried out through a questionnaire with a Likert scale of 1-5, as well as a documentation study. The data analysis technique uses Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach through SmartPLS 4.0 software. The results of the study showed that work discipline had an effect on performance assessment, leadership style had an effect on work discipline but did not have a direct effect on performance assessment, and rewards had an effect on work discipline and performance assessment. In addition, work discipline has been shown to mediate the influence of leadership style on performance assessment, but does not mediate the effect of rewards on performance assessment. This research emphasizes the importance of the role of work discipline as a connecting channel between leadership and performance, as well as the need for the management of a reward system that is in line with employee performance achievements. The results of this study also show that the research model has strong predictive ability with an R² value of 78.7% for Work Discipline and 82.3% for Performance Assessment. This study concludes that Leadership Style is the strongest predictor in shaping employee work discipline, and this high discipline then improves employee performance